SERVICES FOR PEOPLE WITH INTELLECTUAL DISABILITIES IN THE REPUBLIC OF MACEDONIA: VISION AND REALITY - Дамовски, Андон (Ревија за социјална политика/Journal of Social Policy, 2015)
The system of social protection of disabled people in the country to its independence generally was conducted by a medical model and developed a system of institutional care. The reforms in the social protection system in the country (after establishing independence), develops and promotes the social protection of disabled people in their place of residence. The process of reforms in the field of social protection was developed in 2003 and the adoption of certain measures and the social protection policies are established in 2004 as a result of legislative initiatives. The new legislative initiatives and regulations created radical changes in the field of social sector by introducing new solutions. Social reforms are based on three new principles of social protection (decentralization, social inclusion and social protection plural), in order to strengthen and adjust the Macedonian system to European and international standards. Approaching european and international conceptions Ministry of Labor and Social Policy, in its policies and strategies embarked on a process of transformation of public services, social protection of people with intellectual disabilities through the processes of decentralization, disinstitutionalisation, privatization and implementation of joint projects NGOs working in the field of social protection. In this paper will be analyzed the active local policies for people with intellectual disabilities, as well as the capabilities and capacity of local government to open these services to people in the community, taking into account the above mentioned principles in social care.